Dietary Selenium Nanoparticles Improved Growth and Health Indices in Asian Seabass (Lates calcarifer) Juveniles Reared in High Saline Water - Hamzeh Mohtashemipour; Takavar Mohammadian; Mansour Torfi Mozanzadeh; Mehrzad Mesbah; Abdolhossein Jangaran Nejad (Aquaculture Nutrition)
A 60-day study was carried out to determine the effect of dietary selenium nanoparticles (SeNP) on growth, digestive enzymes, and health status of Asian seabass (Lates calcarifer, 46.5 ± 0.2 g) juveniles reared in high saline water (48 ppt). Five levels of SeNP were added to a basal diet (45% protein, 15% lipid), including control (0), 0.5 (SeNP0.5), 1.0 (SeNP1), 2 (SeNP2), and 4 (SeNP4) mg SeNP kg−1 diet. Fish were stocked into fifteen 2,000 L tanks (50 fish tank−1) filled with 1,800 L sand-filtered seawater (26.5 ± 1.5°C, 48.0 ± 0.2 ppt) in a flow-through system. Each dietary treatment was performed in three replicates. The growth rate positively increased in both linear and quadratic trends with increasing dietary SeNP level (P<0.05). The liver Se concentration increased with increasing SeNP in diet (P<0.05). Gut total protease, trypsin, chymotrypsin, alkaline phosphatase (ALP), lipase, and α-amylase activities were significantly enhanced in the SeNP4 group compared to the other treatments (P<0.05). Antioxidant capacity improved in fish-fed SeNP2 and SeNP4 diets regarding catalase and superoxide dismutase activities and the liver glutathione content. Serum lysozyme and hemolytic activities and white blood cells’ respiratory burst activity in the control were lower than in fish-fed SeNP-supplemented diets. Serum total protein, globulin, and globulin/albumin ratio in fish-fed SeNP1, SeNP2, and SeNP4 diets were higher than the other groups (P<0.05). The interleukin-10 and granulocyte-macrophage colony-stimulating factor genes’ relative transcription levels in the gut of fish-fed SeNP4 were higher than the other groups. Serum cholesterol, triglycerides, ALP, aspartate aminotransferase, alanine aminotransferase, and lactate dehydrogenase significantly decreased in fish with increasing SeNP content in the diet. In conclusion, supplementing the diet with 4 mg kg−1, SeNP was recommended to improve growth and health indices in L. calcarifer juveniles reared in high saline water (48 ppt).